65‐2: Sensitivity to Peripheral Artifacts in VR Display Systems. Issue 1 (30th May 2018) - Hoffman, David M.; Meraz, Zoe; Turner, Eric
Abstract : We evaluated the visual system's sensitivity to different classes of image impairments that are closely associated with rendering in VR systems. Even in the far periphery, the visual system was highly sensitive to volatile downsampling solutions. Temporally stable downsampling in the periphery was generally acceptable even with sample spacing up to half a degree.